'MY GARDEN IS NOT PRISTINE': AN INTERVIEW WITH LINDA CATLIN SMITH. (3rd March 2017) - Höstman, Anna
ABSTRACT: Linda Catlin Smith was born in 1957 and grew up in New York. She studied composition in New York and at the University of Victoria, before settling in Toronto in 1981. Linda has received Canada's prestigious Jules Léger prize for her work Garland (2005). She was the Artistic Director of Toronto's contemporary ensemble Arraymusic (1988–93), and a founding member of the interdisciplinary collective Urge (1992–2006). She currently teaches composition at Wilfrid Laurier University. I sat down with Linda in the summer of 2016 at her home in the Trinity Bellwoods neighbourhood of Toronto to ask her about her life and work.